2021
DOI: 10.15407/zoo2021.02.121
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Arthropod Fauna in Flooded Plains of Northern Patagonia (38° S, Araucania Region Chile)

Abstract: In northern Patagonia, there is a kind of water body characterized as flooded plains (vegas), resulting from heavy rains. They have submerged vegetation that sustains aquatic insects and crustaceans, including burrowing crayfish of the genus Parastacus. The object of the present study was to present the first description of the community structure of three such water bodies. The results revealed the existence of seven species in the only site with Parastacus pugnax Poeppig, 1835, whereas in the sites where P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Th e exposed results denote new fi ndings, that confi rm the colonization of zooplanktonic cladocerans and copepods in ground waters and revealed more detailed data on invertebrate communities in comparison to the fi rst descriptions of De los Ríos-Escalante et al (2021). However, more research is needed to understand patterns in community ecology.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Th e exposed results denote new fi ndings, that confi rm the colonization of zooplanktonic cladocerans and copepods in ground waters and revealed more detailed data on invertebrate communities in comparison to the fi rst descriptions of De los Ríos-Escalante et al (2021). However, more research is needed to understand patterns in community ecology.…”
Section: Resultssupporting
confidence: 57%
“…During the rainy season (June-August), they come to the surface or to shallow zones, and aft er the end of the rainy season, in spring, summer and autumn, individuals are hidden in deep zones of their galleries (Rudolph, 2013 a, b). Th e associated communities of the habitats are poorly studied, with the exception of native forest wetlands at 38° S, where crustaceans such as amphipod Hyalella patagonica (Cunningham, 1871), isopod Heterias exul (Mueller 1892) and decapod Aegla araucaniensis (Jara, 1980) (Correa-Araneda et al, 2017) with high aquatic insect diversity (Correa-Araneda et al, 2021) were reported as associated fauna, which would be similar to the fi rst descriptions of fl ooded plains at the same latitude ( De los Rios Escalante et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation